2013
DOI: 10.1021/la400809a
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Rate Effects on the Microstructure, Solid Content, and Rheological Properties of Organogels of Amides Derived from Stearic and (R)-12-Hydroxystearic Acid in Vegetable Oil

Abstract: Using safflower oil as the liquid phase, we investigated the organogelation properties of stearic acid (SA), (R)-12-hydroxystearic acid (HSA), and different primary and secondary amides synthesized from SA and HSA. The objective was to establish the relationship between the gelator's molecular structure, solid content, and gels' microstructure that determines the rheological properties of organogels developed at two cooling rates, 1 and 20 °C/min. The results showed that the presence of a 12-OH group in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 33 publications
6
57
1
1
Order By: Relevance
“…The formation of such crystalline particles by CLW is attributed to a high proportion of linear hydrocarbons (n-alkanes) as reported previously [15]. In addition, the formation of gels with higher elasticity at lower crystalline mass fraction is in agreement with previously reported studies on CLW-oil oleogels [6,16].…”
Section: Minimum Gelling Concentration and Microstructuresupporting
confidence: 91%
“…The formation of such crystalline particles by CLW is attributed to a high proportion of linear hydrocarbons (n-alkanes) as reported previously [15]. In addition, the formation of gels with higher elasticity at lower crystalline mass fraction is in agreement with previously reported studies on CLW-oil oleogels [6,16].…”
Section: Minimum Gelling Concentration and Microstructuresupporting
confidence: 91%
“…Recently, a different long spacing of 12-HSA was reported by some researchers. A different long spacing at different cooling rates was reported by Weiss et al by using safflower oil as a solvent [9]. However, their result is slightly different from ours.…”
Section: Resultscontrasting
confidence: 87%
“…Therefore, the sol-gel transition of the gel is thermally reversible, i.e., the crystalline aggregates melt at high temperatures, while they are formed by crystallization again upon cooling temperature. Structural morphology of the aggregates is significantly affected by thermal history in gelation [9] or solvents used [10]. Terech et al showed that the crosssectional morphology of the fibrillar aggregates had a variety of shapes such as rod-like aggregates with circular or rectangular cross section, lamella-like aggregates, or helical aggregates by different solvents [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, systems where triacylglycerol solvents (vegetable oils) are gelled using natural components, have found potential applications in biorelated fields such as drug delivery, 5−7 cosmetics, 8−10 and foods. 11−13 Among various gelators explored for gelling vegetable oils, natural waxes are considered to be the most promising ones because of their excellent oil binding properties, 14 economical value (capable of gelling oils at a significantly lower mass fractions, w c ≪ 0.1), 15,16 and availability of a number of waxes approved for use in humans. 17,18 Moreover, the gels formed using waxes have interesting properties such as themoreversibility 19,20 and emulsion stabilization, 21−23 which further justifies their popularity as organogelators for vegetable oils.…”
Section: ■ Introductionmentioning
confidence: 99%